Revelation of mechanisms associated with strengthening plant cold tolerance through using exogenous substances - Feng, Di; Zhang, Mingxia; Xu, Jianhua; Gao, Qian; Liu, Jiao; Li, Caixia; Sun, Xiaoan; Xu, Wanli (Frontiers in Plant Science, 2025)
Cold stress (CS) is one of the main factors that limits the crop or plant growth and development in many regions of the world. Many researchers have been endeavoring to break the natural temperature barrier to grow plants in extremely cold areas or to alleviate erratic cold devastation on crops in temperate or subtropical regions for years. Numerous studies and research papers published recently for the last two decades have proven that exogenous substances (ESs) are effective and practical in helping plants tolerate CS. Here, we systematically summarize and characterize all 72 ESs that have been tried against CS, analyze research hotspots in the Web of Science database from 2000 to 2024 using VOSviewer with the keywords “cold stress” and “exogenous substances”, and grouped them accordingly. Based on their underlying mechanisms, five categories of ESs are clearly defined, described and discussed: 1) enhancement of cell osmotic adjustment, 2) improvement of antioxidant pathways, 3) involvement in phytohormone regulation, 4) promotion of photosynthesis; 5) enrichment of nutritional status. After clarifying these five categories, a detailed plant responses and their possible interactions through a signal cross-talk are proposed and followed by discussions on future perspectives on using ESs to fortify plants against CS. The accumulative knowledge and information provided here will be ultimately used to increase plant productivity and agricultural sustainability under CS through chemical and microbial approaches.